European survey of newborn bloodspot screening for CF: opportunity to address challenges and improve performance - Munck, Anne; Berger, Daria O.; Southern, Kevin W.; Carducci, Carla; de Winter-de Groot, Karin M; Gartner, Silvia; Kashirskaya, Nataliya; Linnane, Barry; Proesmans, Marijke; Sands, Dorota; Sommerburg, Olaf; Castellani, Carlo; et al. (Journal of cystic fibrosis, 2023)
Background - The aim of this study was to record the current status of newborn bloodspot screening (NBS) for CF across Europe and assess performance. - Methods - Survey of representatives of NBS for CF programmes across Europe. Performance was assessed through a framework developed in a previous exercise. - Results - In 2022, we identified 22 national and 34 regional programmes in Europe. Barriers to establishing NBS included cost and political inertia. Performance was assessed from 2019 data reported by 21 national and 21 regional programmes. All programmes employed different protocols, with IRT-DNA the most common strategy. Six national and 11 regional programmes did not use DNA analysis. - Conclusions - Integrating DNA analysis into the NBS protocol improves PPV, but at the expense of increased carrier and CFSPID recognition. Some programmes employ strategies to mitigate these outcomes. Programmes should constantly strive to improve performance but large datasets are needed to assess outcomes reliably.
Available online 10 November 2022, version of record 7 June 2023
Gesehen am 29.08.2023